Mechanical pre-treatment of source-collected municipal biowaste prior to energy recovery by anaerobic digestion. (April 2022) - Moreira de Oliveira, Mariana; Moretti, Paul; Malinowsky, Carina; Bayard, Rémy; Buffière, Pièrre; Borges de Castilhos Júnior, Armando; de Araujo Morais Júnior, Joacio; Athayde Júnior, Gilson Barbosa; Gourdon, Rémy
Abstract: Pre-treatments are usually necessary to prepare biowaste to anaerobic digestion. The major objectives are (i) to remove undesirable materials such as plastics and metals, which may contaminate the biowaste even if separated source-collection systems are implemented, and (ii) to extract the most readily biodegradable organic fractions from the waste stream. In this study, two wet mechanical pre-treatments, namely air-compressed press and worm screw press, were investigated on urban household biowaste. Two liquid to solid ratios were tested in each pre-treatment. Anaerobic digestion of pre-treated biowaste was studied by measuring their biomethane potentials and by controlled experiments in a continuously stirred-tank reactor with a feed load of 3.5 gVS.L −1 .d −1 . It was observed that increasing liquid to solid ratio in the pre-treatments allowed to increase the proportion of biodegradable organic matter extracted from the biowaste, up to 949 gCOD.kgTS −1 from household biowaste. The biomethane potentials of pre-treated waste were very high (up 525 LCH4 .kgVS −1 ) and COD (949 gCOD.kg −1 TS) from household biowaste. Anaerobic digestion in continuously stirred-tank reactor showed a very strong conversion of COD load (81%) and a high methane production up to 345 LCH4 .kgVS −1 . Graphical abstract: Image 1 Highlights: Pretreatment systems to extract easily biodegradable compounds were investigated. Two pressing technologies were tested: air-compressed press and worm screw press. The water addition increases organic matter extraction from solid waste. Household biowaste pressed was treaded along with supermarkets biowaste. Anaerobic digestion process showed a high methane production and COD conversion.